1991
DOI: 10.1038/clpt.1991.28
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope studies of nicotine kinetics and bioavailability

Abstract: The stable isotope-labeled compound 3',3'-dideuteronicotine was used to investigate the disposition kinetics of nicotine in smokers, the systemic absorption of nicotine from cigarette smoke, and the bioavailability of nicotine ingested as oral capsules. Blood levels of labeled nicotine could be measured for 9 hours after a 30-minute intravenous infusion. Analysis of disposition kinetics in 10 healthy men revealed a multiexponential decline after the end of an infusion, with an elimination half-life averaging 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 0 publications
4
75
0
1
Order By: Relevance
“…Thus, cotinine reflects longterm, rather than recent, ETS exposure (Rosenberg et al, 1980). Benowitz et al (1991) reported that cotinine has limited use as a biomarker because the metabolism of cotinine differs among individuals and because there is no standard analysis method. However, cotinine has been used as a biomarker for direct and passive smokers' nicotine intake because of its consistently high sensitivity and specificity (Baranowski et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cotinine reflects longterm, rather than recent, ETS exposure (Rosenberg et al, 1980). Benowitz et al (1991) reported that cotinine has limited use as a biomarker because the metabolism of cotinine differs among individuals and because there is no standard analysis method. However, cotinine has been used as a biomarker for direct and passive smokers' nicotine intake because of its consistently high sensitivity and specificity (Baranowski et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The usual systemic absorption of nicotine from a cigarette is 1-1.5 mg but can be as high as three milligrams per cigarette with very intense smoking. 6 In experimental studies in which cigarette smoking is measured and in which nicotine and cotinine pharmacokinetic parameters are characterized, the typical cotinine concentration per cigarette is 12 ng/mL. 5 Assuming this refl ects an intake of one milligram of nicotine, one can estimate a cotinine level of 36 ng/mL for a person taking in 3 mg nicotine from each cigarette.…”
Section: Methodsmentioning
confidence: 99%
“…At this time, there is no pill form of nicotine replacement therapy because the higher doses required to overcome first-pass metabolism may cause nausea and diarrhea due to gastrointestinal irritation (Benowitz et al, 1991). Oral administration of even low doses (4 mg) of nicotine to those genetically deficient in CYP2A6 increased nicotine AUC by over 3-fold (Xu et al, 2002), suggesting that inhibition of nicotine metabolism can make nicotine orally bioavailable.…”
Section: Inhibition Of Nicotine Metabolism By Selegiline 997mentioning
confidence: 99%